TINGKAT PENDIDIKAN PENGAJAR, SARANA PENDIDIKAN, DAN LINGKUNGAN PENDIDIKAN UNTUK MENINGKATKAN KUALITAS LULUSAN SLTP DI KABUPATEN SUKOHARJO - Suyatno ZA (Universitas Sebelas Maret, 2008)
The objectives of this research are: (1) to reveal how teacher's education levelcan affect the quality of students of SLTP in Sukoharjo regency; (2) to describe how farthe school facilities can effect the students' quality; (3) to detect how far external environmentmeans can affect students' quality of SLTP in Sukoharjo regency. The hypothesismade was that there is a significant correlation between teacher’s education level andquality of graduated students of SLTP in Sukoharjo regency. The researcher used descriptiveanalysis to support this research, and used questionnaires to collect the data.Quota-sampling method is used to determine 30 SLTPs as samples and 10 teachers inevery SLTP to be respondents. Based on the data analysis, F value (8.244) was greaterthan F table, so Ho was rejected. It means that there is a significant correlation betweeneducation and quality of graduated students of the SLTP in Sukoharjo regency with thelevel of significance 5 percent. Based on the data analysis results, the researcher suggeststhat the policy makers on education should implement continuous improvement on thequality of teaching learning process by maintaining qualified teacher with minimumbachelor degree and upgrading course.